2017
DOI: 10.1007/s10869-017-9520-y
|View full text |Cite
|
Sign up to set email alerts
|

Work-Life Boundaries and Well-Being: Does Work-to-Life Integration Impair Well-Being through Lack of Recovery?

Abstract: Against the backdrop of increasingly blurred boundaries between work and nonwork, the purpose of this study was to investigate the implications of employees' work-to-life boundary enactment for well-being. Using border/boundary theory (as reported by Ashforth, Kreiner, Fugate (Academy of Management Review 25(3):472-491, 2000) and Clark (Human Relations 54(6):747-770, 2000)) and the effort-recovery model (as reported by Meijman Mulder (Handbook of work and organizational psychology vol. 2 55-53, 1998)), we deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
1
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(148 citation statements)
references
References 59 publications
4
104
1
16
Order By: Relevance
“…For example, in a daily diary design examining a group of construction workers over 21 consecutive weeks, work–life evaluations related to conflict and enrichment were significantly predicted by recovery opportunities across time (Lingard, Francis, & Turner, ). Another study also found that recovery activities also predicted overall satisfaction with work–life balance (Wepfer, Allen, Brauchli, Jenny, & Bauer, ). There is also some evidence that workplace telepressure may infringe on opportunities employees have to recover, and those who report higher levels of workplace telepressure also report less psychological detachment from work (i.e., mental distance from work‐related thoughts; Barber & Santuzzi, ; Santuzzi & Barber, ).…”
Section: Workplace Telepressure and Work–life Balancementioning
confidence: 91%
See 1 more Smart Citation
“…For example, in a daily diary design examining a group of construction workers over 21 consecutive weeks, work–life evaluations related to conflict and enrichment were significantly predicted by recovery opportunities across time (Lingard, Francis, & Turner, ). Another study also found that recovery activities also predicted overall satisfaction with work–life balance (Wepfer, Allen, Brauchli, Jenny, & Bauer, ). There is also some evidence that workplace telepressure may infringe on opportunities employees have to recover, and those who report higher levels of workplace telepressure also report less psychological detachment from work (i.e., mental distance from work‐related thoughts; Barber & Santuzzi, ; Santuzzi & Barber, ).…”
Section: Workplace Telepressure and Work–life Balancementioning
confidence: 91%
“…Another study also found that recovery activities also predicted overall satisfaction with work-life balance (Wepfer, Allen, Brauchli, Jenny, & Bauer, 2018). There is also some evidence that workplace telepressure may infringe on opportunities employees have to recover, and those who report higher levels of workplace telepressure also report less psychological detachment from work (i.e., mental distance from workrelated thoughts; Barber & Santuzzi, 2015;Santuzzi & Barber, 2018).…”
Section: Workplace Telepressure and Work-life Balancementioning
confidence: 92%
“…A growing research body has dealt with potential implications of increased work-to-nonwork integration for employee health and well-being, yet findings remain inconclusive (Allen, Cho, & Meier, 2014;Rothbard & Ollier-Malaterre, 2016): While work-to-nonwork integration allows for positive spillover and enrichment (e.g., Powell & Greenhaus, 2010), work-to-nonwork integration also facilitates negative spillover and conflict (e.g., Hecht & Allen, 2009;Kossek, Ruderman, Braddy, & Hannum, 2012;Powell & Greenhaus, 2010;Wepfer, Allen, Brauchli, Jenny, & Bauer, 2018).…”
mentioning
confidence: 99%
“…Происходит радикализация теории границ: размывание разделения сфер труда и личной жизни ведет не только к конфликту, но и к посягательству академии на частную жизнь, подавлению личных интересов «эксплуататорской академи ческой средой» [Hampson et al, 2014]. Более подробно раскрываются условия функционирования границ, восприятие которых может меняться в зависимости от направления: от работы к неработе и от неработы к работе [Wepfer et al, 2018].В рамках второго поколения исследований теория границ дополняется теорией ролевых конфликтов [Hampson, 2018;Beigi et al, 2016], обогащения [NealeMcFall et al, 2018], гендерных различий [Toffoletti, Starr, 2016;Smidt et al, 2017], технологизации и инновационности [Wepfer et al, 2018;. Также активно развивается интерсекциональный подход при изучении баланса жизни и труда в академии [Haskins et al, 2016;Beigi et al, 2016].…”
Section: методология обзора литературыunclassified
“…В условиях сжатого академического времени баланс жизни и труда освещается с позиции охраны личного времени [Albright, Petrulis, 2007]. Дискурс баланса жизни и труда в академиях сводится к функционированию семьи [Hawkins et al, 2014;Hermann et al, 2014;Beigi et al, 2016;McCutcheon, Morrison, 2016] и индивидуальному благополучию [Perrakis, Martinez, 2012;Levin et al, 2017;Young et al, 2017;Wepfer et al, 2018], а также первостепенно лежит в области женского индивидуального карьерного выбора [Mavriplis et al, 2010;Hermann et al, 2014;Beddoes, Pawley, 2014;Waljee et al, 2015;Rohde et al, 2016;Baader et al, 2017], который не всегда оказывается личным и сопрягается с социальными ожиданиями, приоритетом карьеры партнера [Beddoes, Pawley, 2014]. Лимитирование амбици озности женщин подкрепляется конструкцией укорененных условий, построенных на системе социокультурных стереотипов (на женщину возлагается ответственность за благополучие семьи), тогда как для мужчин действует иной конструкт -выбор, независимая расстановка приоритетов [Smidt et al, 2017].…”
Section: формирование аналитической основыunclassified